The Ins and Outs of Employment in 25 OECD Countries - Garda, Paula (OECD Economics Department Working Papers, 2016)
This paper presents quantitative information on labour market flows for 25 OECD countries. It uses household surveys that offer the advantage of reporting monthly transitions between employment, unemployment and economic inactivity for individuals. Between 2005 and 2012, the annual probability of leaving employment averaged 10% across OECD countries. Jobless people have a 30% average probability of finding a job. The analysis uncovers significant cross-country differences and highlights key facts about how labour market flows differ depending on socio-demographic, worker characteristics and the institutional framework. Female, young, low educated and low income workers are at highest risk of becoming jobless. Young jobless individuals have higher chances of finding a job than their older counterparts. Female, low educated and low income jobless individuals face a lower probability of finding a job than others